Exercise Training During Working Hours at a Hospital Department: A Pilot Study. Issue 11 (20th November 2022) - Molsted, Stig; Justesen, Just Bendix; Møller, Sofie Fønsskov; Særvoll, Charlotte Ahlgren; Krogh-Madsen, Rikke; Pedersen, Bente Klarlund; Fischer, Thea Kølsen; Dalager, Tina; Lindegaard, Birgitte
Abstract : This pilot study found that 37% of invited employees in a medical department on a hospital completed an exercise training program of 12 weeks. Despite low training adherence, the completers improved aerobic capacity and other objectively tested health parameters as well as self-rated health including muscular skeletal pain. Abstract : Objectives: This pilot study tested the use of an exercise offer to hospital employees during working hours and changes in work and health parameters. Methods: Employees (n = 214) from a medical department on a Danish hospital were invited to 30 minutes' exercise training twice weekly for 12 weeks. Outcomes included health- and work-related parameters. Results: Eighty employees (mean age, 44.4 [SD, 10.7] years; 81.3% women) completed the study. Intervention adherence was 36.3% (SD, 25.1%). Aerobic capacity increased from 34.6 (95% confidence interval [CI], 32.3 to 36.9) to 36.7 (95% CI, 34.1 to 39.4) mL O2 /min per kilogram, P = 0.004. Blood pressure decreased from 120 (95% CI, 117 to 123)/79 (95% CI, 76 to 81) to 116 (95% CI, 112 to 120)/76 (95% CI, 74 to 79) mm Hg, P = 0.003. Waist circumference and musculoskeletal pain decreased. Well-being, social capital, and quality of life increased. Conclusions: Despite low training adherence, completers improved outcomes related to metabolic and self-rated health.